Hubungan Risiko Bisnis dengan Financial Leverage - Bahgia, Saiful (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study aims to test the relationship between business risk and financial leverage in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The data analysis method in this study uses multiple linear regression to predict the influence of independent variables. The population in this research is a manufacturing company listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling method in this study is the purposive sampling method. The results showed a relationship between business risk and financial leverage; this shows that the higher the business risk, the higher the company's financial leverage, so the company will be more careful in using sources of funds from debt.